PENGARUH KEPEMIMPINAN KEPALA SEKOLAH YANG MEMBERDAYAKAN TERHADAP KINERJA GURU PAUD - Milawati; A. Suriansyah; Purwanti, Ratna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the influence of empowering school principal leadership on the performance of early childhood education (PAUD) teachers. This research uses a library research approach by analyzing relevant national and international academic sources. The results show that empowering leadership styles significantly contribute to improving motivation, professionalism, and teacher performance. Principals who apply transformative, collaborative, and contextual leadership are proven to create positive learning environments, enhance teaching innovation, and strengthen school-community partnerships. This study recommends the need to strengthen leadership capacity in early childhood education institutions to foster adaptive and empowering organizational cultures.